Biodiversity assessment of spiders in Singapore's parks and gardens. - Law, Kymberly Ariel Yen Theng. (2012)
A rapid biodiversity assessment of spiders was carried out to better understand the biodiversity of spiders in Singapore. Spiders were collected during a time period of January – March 2012 from six parks and gardens in Singapore, namely Admiralty Park, Ang Mo Kio Town Garden West, Bukit Batok Nature Park, East Coast Park, Singapore Botanic Gardens and West Coast Park. Three methods of collection, active searching, leaf litter sorting and beating were used. A total of 1643 spiders with 110 species, 82 genera from 25 families were recorded with Tetragnathidae (16%) and Salticidae (15%) being the most abundant families. The calculation of diversity indices revealed that Singapore Botanic Gardens, the only site with primary rainforest had the highest overall biodiversity with the highest richness (S) value of 18±2.163 and diversity (H’) value of 2.562±0.092. Although West Coast Park showed the lowest diversity and richness values, it had the highest evenness (E) value of 0.933±0.013. Similarity analysis revealed that Admiralty Park and Ang Mo Kio Town Garden West have the most similar spider faunas. The results obtained here would serve as data for comparison with previously collected data and for future reference in spider biodiversity research and conservation efforts.